A polydopamine-mediated biomimetic facile synthesis of molybdenum carbide-phosphide nanodots encapsulated in carbon shell for electrochemical hydrogen evolution reaction with long-term durability. (15th October 2019) - An, Tae-Yong; Surendran, Subramani; Kim, Hyunkyu; Choe, Woo-Seok; Kim, Jung Kyu; Sim, Uk
Abstract: Biomimetic environmental benign synthesis of electrocatalysts with inexpensive transition metal compounds is a promising approach to achieve clean hydrogen production with high sustainability via water splitting. Herein, a mussel-inspired facile synthesis of N-carbon encapsulated molybdenum carbide-phosphide (Mo2 C–MoP) hybrid nanodots using a polydopamine biopolymer for efficient hydrogen evolution reactions (HERs), and long-term durability is demonstrated. The unique properties of polydopamine facilitate the transition metal ions (i.e., molybdenum) chelation without the use of additional toxic chelating agents. In the presence of phosphate buffer solution, the anchoring properties of polydopamine induce the formation of molybdenum-based complexes with the carbon and phosphide species, resulting in the synthesis of Mo2 C–MoP hybrid nanodots encapsulated in nitrogen-doped carbon shell. Consequently, the Mo2 C–MoP hybrid nanodots exhibit considerable electrocatalytic HER performance and long-term stability. The low overpotential of 147 mV is obtained at the high current density of 20 mA cm −2 along with the low Tafel value of 64.92 mV dec −1 in alkaline medium. Furthermore, the long-term stability over 120 h is achieved using Mo2 C–MoP@CP. Therefore, the use of an environment-friendly biopolymer for the fabrication of noble-metal-free, efficient, and stable HER electrocatalysts can be a promising strategy to achieve sustainable and clean H2 production. Graphical abstract: Image 1 Highlights: Polydopamine-mediated biomimetic synthesis of noble-metal-free Mo2 C–MoP electrocatalyst encapsulated in a carbon shell. Chelation of transition metal ions and formation of an unassisted anchoring without the use of additional toxic agents. Conformal passivation of Mo2 C–MoP hybrid nanodots with carbon shell from the carbonization of polydopamine. High efficient hydrogen evolution reaction with long-term durability over 120 h in alkaline media.